Virality and the Virus: COVID-19 Cures on Twitter in India - Mishra, Dibyendu; Akbar, Syeda Zainab; Shekhawat, Gazal; Pal, Joyojeet (Hawaii International Conference on System Sciences (HICSS), 2022)
Social media platforms often become environments of information ambiguity during crisis events. We studied the discussion around four ”cures” for COVID-19 in India, where the highest number of cases were recorded between 2020 and May 2021, focusing on the role played by high network accounts on social media such as those of journalists, politicians, and celebrities. We find that information scarcity and anxiety among citizens enabled non-experts, particularly the aforementioned social media influencers. We find that this undermined institutional sources of information and led to massive spikes in online interest around unproven cures during the peak of the crisis.